2010
DOI: 10.1080/00071668.2010.496446
|View full text |Cite
|
Sign up to set email alerts
|

The effect of feeding essential oils on broiler performance and gut microbiota

Abstract: 1. In this study the effect of a blend of essential oils (EO) comprising 15 g/tonne thymol and 5 g/tonne cinnamaldehyde on the performance and intestinal microbiota of broilers was investigated. 2. A total of 720 male Ross broilers were divided into two dietary treatments with 12 replicate pens per treatment. Broilers were given a control soybean-wheat-based diet with or without added EO in two diet phases (0-21 d and 22-42 d). 3. The blend of EO increased body weight gain of broilers from 0 to 42 d by 45%. 4.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
99
2
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(122 citation statements)
references
References 39 publications
14
99
2
7
Order By: Relevance
“…Regarding the influence of A. annua extracts on broiler performance, the literature is scarce. Different plant-derived essential oils have antimicrobial and antioxidant properties and their application as feed additives in broiler nutrition has been studied for some time (Lee et al, 2003;Lee et al, 2004;Brenes & Roura, 2010;Tiihonen et al, 2010). It is reasonable to assume that the effects of essential oils on broiler performance vary depending on the type of the oil as well as the quality and quantity of the active components (Tiihonen et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the influence of A. annua extracts on broiler performance, the literature is scarce. Different plant-derived essential oils have antimicrobial and antioxidant properties and their application as feed additives in broiler nutrition has been studied for some time (Lee et al, 2003;Lee et al, 2004;Brenes & Roura, 2010;Tiihonen et al, 2010). It is reasonable to assume that the effects of essential oils on broiler performance vary depending on the type of the oil as well as the quality and quantity of the active components (Tiihonen et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Different plant-derived essential oils have antimicrobial and antioxidant properties and their application as feed additives in broiler nutrition has been studied for some time (Lee et al, 2003;Lee et al, 2004;Brenes & Roura, 2010;Tiihonen et al, 2010). It is reasonable to assume that the effects of essential oils on broiler performance vary depending on the type of the oil as well as the quality and quantity of the active components (Tiihonen et al, 2010). The majority of experimental results indicate a reduced feed intake at largely unchanged body weight gain or final body weight, thus resulting in an improved feed conversion ratio, when feeding essential oils (Brenes & Roura, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Medicinal plant supplementation to poultry diets improved feed efficiency in the study by Hong et al (2012), whereas their effect on feed consumption and body weight gain were not consistent with previous findings. In an earlier study, an improvement in body weight and gain was observed when birds were fed diets with thyme (Tiihonen et al, 2010).…”
Section: Hen Productive Performancementioning
confidence: 99%
“…Similar effects were found by Cho et al (2014) when phytogenic additives were included in the diet of chickens. Other studies showed improvements in BW at 21 and 42 days when the chickens were fed peppermint, thyme leaves, and thymol with cinnamaldehyde or carvacrol (Ocak et al, 2008;Tiihonen et al, 2010;Mohiti-Asli and Ghanaatparast-Rashti, 2015;Hashemipour et al, 2016). In the present study, feed intake was different at days 21 and 1-42 (P<0.01), as well as at 28 and 35 days (P<0.05), in which the oxytetracycline treatment group consumed less feed, followed by MOO treatment group, while control group had the highest FI throughout the study (1-42 days) ( Table 2).…”
Section: Resultsmentioning
confidence: 98%